PERMASALAHAN TENTANG BATAS WAKTU PENDAFTARAN PERALIHAN HAK MILIK ATAS TANAH KARENA PEWARISAN DI BADAN PERTANAHAN NASIONAL KOTA SAMARINDA. - Apriadin Apriadin (Universitas 17 Agustus 1945 Samarinda, 2014)
Abstract That according to Article 61 paragraph 3 of Government Regulation No. 24 of 1997 states that: If a person has the right to land had died then right as heir must register their rights within a period of 6 (six) months after the death of the person, not charged pendaftaran.Dari fee provisions of article above that the presence of legal events in the form of inheritance, it can be said that the heir who receives the transfer of property rights as heir must register their rights transition to the Office of National Defence. Within a period of 6 (six) months after the death of the testator must be registered, it is intended that the issuance of new certificates can on behalf of the heirs in question and that the certainty and legal protection for holders of the new property. That the implementation of the registration of transfer of rights because inheritance is done directly by the rights holder / or heirs to the National Land Office, accompanied by the documents that must be satisfied that the respondent completing the registration of property rights for inheritance transition is done through the ravine by 18 respondents or 60% who do request through the intermediary of notary services as much as 7 respondents or 23.334% and the register transfer of rights as an individual inheritance as much as 5% of the respondents, or 16,667.